ADOLF HITLER AND THE GENOCIDE AGAINST ROMA, SERBS AND JEWS DURING WORLD WAR II (Heritage, 2020)
Numerous bloody wars and conflicts have been fought throughout world history, but World War II was the most devastating and generally produced the greatest losses in human, material, infrastructural, cultural and state resources. Undoubtedly the biggest culprit for this, almost catastrophic scenario, was Adolf Hitler. He, together with his associates, started a conflict that will pay millions, people with their lives, misery, misfortune and concentration camps.This semi-educated failed painter, non-worker, mediocrity and fanatical admirer of Germanic mythology and Wagner in the 1930s. century from idlers and bohemians turned into the most mentioned person in recent history.Because of his fantasies and illusions about racial superiority, he pushed Germany into a catastrophe from which it recovered decades after the end of the war, and turned the swastika - an old Hindu symbol that personifies the Sun and fertility, ie life - into the most hated thing in human history.In its systematic approach to killing millions of men, women and children, carried out by a civilized nation, that rule was one of the most horrific in history. How could an entire nation allow itself to be ruled in such a way? How could it happen that no one knows what is happening in front of their own door? Did Germany be inhabited by millions of little Hitler - men, women who each in their own way nurtured the same hatred as their Führer? A heated debate on this has been going on for a long time and will certainly continue in the future.Adolf Hitler tried to impose his vision of the world based on racial inequality. His reign is one of the darkest periods in world history.
Keywords: Adolf Hitler's childhood, political career, Nazi regime, World War II (Rise, defeat and death)